2012
DOI: 10.1029/2011jd017117
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal tides from the troposphere to the lower mesosphere as deduced from TIMED/SABER satellite data and six global reanalysis data sets

Abstract: We compare and examine diurnal temperature tides including their migrating component (DW1) from the troposphere to the lower mesosphere, using data from Thermosphere-Ionosphere-Mesosphere-Energetics and Dynamics/Sounding of the Atmosphere using Broadband Emission Radiometry (TIMED/SABER) and from six different reanalysis data sets: (1) the Modern Era Retrospective analysis for Research and Applications (MERRA), (2) the European Centre for Medium-range Weather Forecasts (ECMWF) reanalysis (ERA-Interim) (3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
67
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 60 publications
(81 reference statements)
15
67
0
Order By: Relevance
“…Sakazaki et al [2012] report that MERRA reproduces stratospheric diurnal temperature tides well. Also, in this study, we confirmed that diurnal temperature tides in MERRA are consistent with observational data from GPS radio occultation (GPS-RO) measurements with the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) [Anthes et al, 2008] (not shown).…”
Section: Appendix B: Comparison Of the Smiles Saber And Ctm Datasetsmentioning
confidence: 93%
See 4 more Smart Citations
“…Sakazaki et al [2012] report that MERRA reproduces stratospheric diurnal temperature tides well. Also, in this study, we confirmed that diurnal temperature tides in MERRA are consistent with observational data from GPS radio occultation (GPS-RO) measurements with the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) [Anthes et al, 2008] (not shown).…”
Section: Appendix B: Comparison Of the Smiles Saber And Ctm Datasetsmentioning
confidence: 93%
“…This suggests that vertical transport by the diurnal tide, which is mainly generated in the troposphere and propagates into the stratosphere [Chapman and Lindzen, 1970;Sakazaki et al, 2012, Sakazaki et al, manuscript in preparation, 2013, is the major dynamical factor. The dominance of the diurnal harmonic component (Figure 7d) is explained by the fact that the variations are inversely proportional to the frequency (equation (5)), although the diurnal and semidiurnal harmonic amplitudes of vertical winds are comparable between 20 and 50 km (Figure 7e).…”
Section: Photochemical and Dynamical Contributions To Diurnal Ozone Vmentioning
confidence: 99%
See 3 more Smart Citations